Effect of initial curing conditions on air permeability and de- icing salt scaling resistance of surface concrete - Zhang, Meng; Sakoi, Yuki; Aba, Minoru; Tsukinaga, Yoichi (Journal of Asian Concrete Federation, 2019)
Enhancing the surface quality of concrete is a key to improve the durability of reinforced concrete. Surface concrete can protect steel bars from corrosion due to the migration of gas, water and ion from the surrounding environment. Therefore, the influence of the initial curing on air permeability and the de-icing salt scaling resistance of surface concrete were investigated in this paper. Firstly, existing bridge structures in the cold region of Japan were surveyed with visual rating and non-destructive test (NDT) for the surface quality of concrete. Secondly, the concrete specimens were prepared for different curing conditions and methods including cold weather concreting, heat or non-heat-supply curing, ex- tending demold period and water-retention sheet. These results showed that concrete curing with sheet or permeability formwork was better than curing in air. Especially, utilizing permeability formwork is greatly effective for the attainment of high surface quality of concrete. Simultaneously, focus on cold weather concreting, could evaluate the appropriate curing period combining with the surface air perme- ability and the de-icing salt scaling resistance of concrete. The surface concrete has better de-icing salt frost resistance, when the surface air permeability coefficient is below 1×10-16m2 or the initial curing period is more than three weeks.